TAFSIR AQIDAH TENTANG NERAKA (TAFSIRAN TERHADAP QS. AL-NISA/4: 14) - Tasmin Tangngareng; I Gusti Bagus Agung Perdana Rayyn; Al-Fiana Mahar (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
This article discusses the aqidah interpretation of QS. al-Nisa/4:14 which explains about hell. In this article there are several important topics that will be the focus of the discussion, namely, first is the study of verses in vocabulary terms, their relation to other arguments and the interpretation of scholars, second is the description of the content of the creed in QS. al-Nisa/4:14. Therefore, it is necessary to explain these things so as not to cause misunderstanding in understanding the verse. The study of this problem was carried out by conducting a literature review with a linguistic approach and an interpretive science approach. So the conclusion is that there are differences of opinion among scholars in understanding and explaining the verse, there are scholars who are more inclined to disobedience, both forms of torture and forms of immorality, there are scholars who interpret that the verse speaks of disbelief in the Shari'a, and there are scholars who tend to interpret that the verse contains an order not to change the decree of Allah swt.